Immunoinformatics Analysis of SARS-CoV-2 Isolated from Karst of Bats in Malang, Indonesia - Moch Irfan Hadi; Aditya Sukma Prawira; Khuliyah Candraning Diyanah; Dedy Suprayogi; Soedjajadi Keman; Yudied Agung Mirasa; M Yusuf Alamudi (Institute of Medico-legal Publications Pvt Ltd, 2021)
In December 2019, cases of mysterious pneumonia were first reported in Wuhan, Initially, the diseasewas temporarily named as 2019 novel coronavirus (2019-nCoV), then WHO announced a new name onFebruary 11, 2020, namely Coronavirus Disease (COVID-19) which is caused by a virus Severe AcuteRespiratory Syndrome Coronavirus-2 (SARS-CoV-2). This virus can be transmitted from person toperson and has spread widely in China and more than 190 other countries and territories. Meanwhile inIndonesia, up to September 2020, 203 thousand cases of COVID-19 were found and 8336 deaths. Batsact as important disease reservoirs for various etiologic agents of disease that can be transmitted betweenspecies, infecting humans and mammals, both domestic and wild. The purpose of this study was to analyzeSARS-CoV-2 immunoinformatics in bats in Karst Malang Indonesia as the basis for making SARS-CoV-2vaccines. This research method is SARS-CoV-2 amino acid bats in Karst Malang, Indonesia analyzed byimmunoinformatics. From the research results, it was found that SARS-CoV-2 protein from Malang Karstbats were antigen, non-allergen and non-toxin, so that they could be used as vaccine candidates, diagnostickits and immunotherapy.